Electrical conductivity of milk as related to daily milk yield of udder quarters in automatically milked cows - BOGUCKI, MARIUSZ (The Indian Journal of Animal Sciences, 2018)
The aim of the study was to determine the frequency of udders with specific levels of milk electrical conductivity and milk yield in primiparous and multiparous cows. Relationships between the health and milk yield of individual udder quarters in the primiparous and multiparous cows were also analysed. The left and right front quarters constituted, respectively, 67.39 and 67.90% of the quarters from which milk with electrical conductivity ≤5.50 mS/ cm was drawn. In the conductivity class >7.00 mS/cm, the right and left rear quarters showed the highest proportions (9.59 and 7.13%, respectively). Individual udder quarters from the cows most often produced either less than 7.00 kg or more than 10.00 kg milk per day. These differences concerned the front and rear udders. In the first two classes of milk electrical conductivity, the frequency of individual udder quarters in the primiparous and multiparous cows was similar. For milk with the lowest electrical conductivity, the values ranged from 50.38% (front left) to 52.62% (rear left) in primiparous cows, and from 47.38% (rear left) to 49.62% (front left) in multiparous cows. As the health of the mammary gland deteriorated, daily milk production of all its quarters was observed to decrease. A more marked reaction to this condition was observed in the front quarters, the yield of which decreased by 3.40 kg (left) and 3.02 kg (right). The rear left quarters decreased their yield by 2.85 kg/day, and the rear right ones by 2.18 kg/day. Higher production levels in all mammary quarters and in every milk electrical conductivity class were noted in the multiparous cows. The increasing milk electrical conductivity was paralleled by a lower daily milk yield of the udder quarters in both primiparous and multiparous cows. For the front left and right quarters, this decrease was 2.77 and 2.41 kg in the youngest cows, and 4.27 and 4.26 kg in the older cows. The decrease in milk production from the rear left quarters was 2.67 kg/day in primiparous and 3.76 kg/day in multiparous cows; the respective values for the rear right quarters were 2.01 and 3.86 kg milk/day.